2014
DOI: 10.18052/www.scipress.com/ilns.16.62
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Elite Phosphate Solubilizing Bacteria from Soil under Paddy Cultivation

Abstract: A considerable number of bacterial species are able to exert a beneficial effect upon plant growth. Mostly they are associated with the plant rhizosphere, so they are called as rhizobacteria. Phosphorus is an essential element for plant development and growth making up about 0.2 % of plant dry weight. Several scientists have reported the ability of different bacterial species to solubilize insoluble inorganic phosphate compounds, such as tricalcium phosphate, dicalcium phosphate, hydroxyapatite, and rock phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The highest solubilizing indices for PK11 and PP20 were 2.935 and 2.870 both observed within the nanoclay + alginate carrier. Previous reports have revealed that the maximum and minimum colony diameter were found with Bacillus species P6 (1.91 mm) and P8 (0.61 mm), which also had the maximum and minimum of halo zone diameters of 5.89 mm and 2.1 mm, respectively ( Gandhi et al., 2014 ). The solubilizing efficiency of two Pseudomonas species (P1 and P2) among different organisms were reported to be 44.44 and 71.43% ( Selvi et al., 2017 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The highest solubilizing indices for PK11 and PP20 were 2.935 and 2.870 both observed within the nanoclay + alginate carrier. Previous reports have revealed that the maximum and minimum colony diameter were found with Bacillus species P6 (1.91 mm) and P8 (0.61 mm), which also had the maximum and minimum of halo zone diameters of 5.89 mm and 2.1 mm, respectively ( Gandhi et al., 2014 ). The solubilizing efficiency of two Pseudomonas species (P1 and P2) among different organisms were reported to be 44.44 and 71.43% ( Selvi et al., 2017 ).…”
Section: Discussionmentioning
confidence: 93%
“…Inoculated plates were incubated in dark at 28 °C and the diameter of the clear zone (halo) and the bacterial growth diameter were measured after 8 days. All assays were replicated three times and solubilization index (SI) calculated by the following formula: SI = Colony diameter + Halo zone diameter/Colony diameter ( Gandhi et al., 2014 ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The zinc solubilizing bacterial isolates produce organic acid which help in solubilization of insoluble zinc compound. Similarly, Gandhi et al, (2014) isolated 240 zinc solubilizing bacterial strains from rhizosphere of rice. Based on the performance of bacterial strains, there were 15 isolates found to be potential zinc solubilizer.…”
Section: Resultsmentioning
confidence: 99%
“…shape, size, elevation, colony structure, surface form, margins and surface texture or color; at 10 -4 , 10 -6 or 10 -8 dilution spreading were noted down and observed for their characterization. [37] …”
Section: Morphologymentioning
confidence: 99%